American College of Rheumatology Provisional Criteria for Global Flares in Childhood‐Onset Systemic Lupus Erythematosus. Issue 6 (25th April 2018) - Brunner, Hermine I.; Holland, Michael; Beresford, Michael W.; Ardoin, Stacy P.; Appenzeller, Simone; Silva, Clovis A.; Flores, Francisco; Goilav, Beatrice; Wenderfer, Scott E.; Levy, Deborah M.; Ravelli, Angelo; Khunchandani, Raju; et al.
Abstract : Objective: To validate the preliminary criteria of global flare for childhood‐onset SLE (cSLE). Methods: Pediatricians experienced in cSLE care (n = 268) rated unique patient profiles; results of standard cSLE laboratory testing and information about the cSLE flare descriptors were presented as follows: global assessment of patient well‐being, physician global assessment of disease activity (MD‐global), Disease Activity Index score, protein/creatinine ratio (PCR), and erythrocyte sedimentation rate (ESR). Using rater interpretation of the course of cSLE (baseline versus followup as the gold standard), performance (sensitivity, specificity, area under the receiver operating characteristic curve [AUC]) of the preliminary flare criteria was tested. An international consensus conference was held to rank the preliminary flare criteria as per the American College of Rheumatology recommendations and delineate threshold scores for minor, moderate, and major flares. Results: The accuracy of the 2 highest‐ranked candidate criteria that consider absolute changes (∆) of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) or British Isles Lupus Assessment Group (BILAG) (numeric scoring: A = 12, B = 8, C = 1, and D/E = 0), MD‐global, PCR, and ESR were confirmed (both AUC >0.93). For the SLEDAI‐based criteria (0.5 × ∆SLEDAI + 0.45 × ∆PCR + 0.5 × ∆MD‐global + 0.02 × ∆ESR) flare scores ≥6.4/3.0/0.6 constituted major/moderate/minor flares, respectively. For the BILAG‐based algorithm (0.4 × ∆BILAG + 0.65 × ∆PCR + 0.5 × ∆MD‐global + 0.02 × ∆ESR) flare scores ≥7.4/3.7/2.2 delineated major/moderator/minor flares, respectively. These threshold values (SLEDAI, BILAG) were all >82% sensitive and specific for capturing flare severity. Conclusion: Provisional criteria for global flares in cSLE are available to identify patients who experienced a flare. These criteria also allow for discrimination of the severity of cSLE exacerbations.